METHODOLOGICAL FOUNDATIONS OF THE STUDY OF THE PROBLEM OF PREVENTING CORRUPTION OFFENSES IN THE MILITARY ADMINISTRATION - Pryimak, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article contains the rationale for the thesis that the prevention of corruption is now one of the priorities in the activities of military command and control bodies. Obtaining objective, reliable and reliable conclusions, proposals and recommendations on this problem largely depends on the correct choice of methods of scientific research. Despite a large number of scientific studies related to the legal principles of combating corruption in all areas of public administration, the article identifies certain patterns of the methods of scientific knowledge used in them. The article proves that the methodology of scientific research of the legal aspects of preventing corruption offenses in military command and control bodies is a set of techniques and methods produced by legal and other sciences, the application of which allows a comprehensive study of the subject of research. An element of the system of research methodology for the prevention of corruption offenses is a method – a special way of carrying out scientific activities, allows you to obtain information and data on certain legal phenomena or processes. The article proves that the study of the legal aspects of preventing corruption offenses in the military command and control bodies requires the use of two groups of methods: general, which are used in all branches of scientific knowledge, and special, inherent exclusively in legal science. The general methods, the use of which would be advisable in the study of the phenomenon of corruption in the aspect of the problems we are considering, include the methods of analysis and synthesis, deduction and induction borrowed from logic, the system-structural method produced in systems theory, the modeling method, and a number of others. These methods represent the methods of scientific knowledge of the phenomenon of preventing corruption, classic for modern legal research. Certain features of the subject of the study of expediency determine the use of synergetic, praxeological, axiological and other methods. The special methods of scientific knowledge of the laws of preventing corruption offenses in the military command and control bodies include historical-legal and comparative-legal methods, as well as formal dogmatic, technical-legal, legal-semantic and other methods inherent in legal sciences.
Keywords: prevention, corruption, military management, security and defense sector, methodology, research methods